2018
DOI: 10.1016/j.colsurfb.2018.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Going through the wine fining: Intimate dialogue between organics and clays

Abstract: Wine chemistry inspires and challenges with its complexity and intriguing composition. In this context, the composites based on the use of a model protein, a polyphenol of interest and montmorillonite in a model hydroalcoholic solution have been studied. A set of experimental characterization techniques highlighted the interactions between the organic and the inorganic parts in the composite. The amount of the organic part was determined by ultraviolet-visible (UV-VIS) and thermal analysis. X-ray diffraction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…Clay minerals have attracted attention in recent years as functional materials owing to their special and different structures, high specific surface areas, and remarkable adsorption capacities [29,30]. They can be used as alternative materials for the immobilization of compounds with photocatalytic properties [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Clay minerals have attracted attention in recent years as functional materials owing to their special and different structures, high specific surface areas, and remarkable adsorption capacities [29,30]. They can be used as alternative materials for the immobilization of compounds with photocatalytic properties [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The low enhancing efficiency of Al_MMT treated with Trp can be explained by the low absorption of Trp of MMT due to the counterbalance of either positive (-NH 2 ) and negative (-COOH) groups in the aminoacidic structure. On the contrary, different studies showed the prompt absorption of BSA at the surface or the edges of MMT by electrostatic and/or chemical interaction [42,43]. Noticeably, while the fluorescent signal measured for Trp was reproducible between different tests (small standard deviation) both in water and with Al_MMT (Figure 7A), the reproducibility between measurements was observed only in water in the case of BSA.…”
Section: Fluorescence-based Detection Of Biomolecules With Al_mmtmentioning
confidence: 92%
“…Aluminum, iron, magnesium and sometimes lithium occupy the octahedral sites, whereas silicon and, in part aluminum occupy tetrahedral sites. Various cations, but specially Na + and Ca 2+ , may occupy interlayer positions [27,28].…”
Section: Introductionmentioning
confidence: 99%